Ash2l interacts with Oct4-stemness circuitry to promote super-enhancer-driven pluripotency network. Issue 19 (26th September 2019) - Tsai, Ping-Hsing; Chien, Yueh; Wang, Mong-Lien; Hsu, Chih-Hung; Laurent, Benoit; Chou, Shih-Jie; Chang, Wei-Chao; Chien, Chian-Shiu; Li, Hsin-Yang; Lee, Hsin-Chen; Huo, Teh-Ia; Hung, Jui-Hung; et al.
Abstract: Pluripotency and cell fates can be modulated through the regulation of super-enhancers; however, the underlying mechanisms are unclear. Here, we showed a novel mechanism in which Ash2l directly binds to super-enhancers of several stemness genes to regulate pluripotency and self-renewal in pluripotent stem cells. Ash2l recruits Oct4/Sox2/Nanog (OSN) to form Ash2l/OSN complex at the super-enhancers of Jarid2, Nanog, Sox2 and Oct4, and further drives enhancer activation, upregulation of stemness genes, and maintains the pluripotent circuitry. Ash2l knockdown abrogates the OSN recruitment to all super-enhancers and further hinders the enhancer activation. In addition, CRISPRi/dCas9-mediated blocking of Ash2l-binding motifs at these super-enhancers also prevents OSN recruitment and enhancer activation, validating that Ash2l directly binds to super-enhancers and initiates the pluripotency network. Transfection of Ash2l with W118A mutation to disrupt Ash2l–Oct4 interaction fails to rescue Ash2l-driven enhancer activation and pluripotent gene upregulation in Ash2l-depleted pluripotent stem cells. Together, our data demonstrated Ash2l formed an enhancer-bound Ash2l/OSN complex that can drive enhancer activation, govern pluripotency network and stemness circuitry.